2001
DOI: 10.1046/j.1365-2958.2001.02363.x
|View full text |Cite
|
Sign up to set email alerts
|

A ComGA‐dependent checkpoint limits growth during the escape from competence

Abstract: In Bacillus subtilis, competence for transformation develops in 5-10% of the cells in a stationary phase culture. These cells exhibit a prolonged lag in the resumption of growth and cell division during the escape from competence. To better understand the basis of this lag, we have characterized competent cultures microscopically. To distinguish the minority of competent cells, a translational fusion between ComK, the competence transcription factor, and the green fluorescent protein (GFP) was used as a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 41 publications
9
161
0
Order By: Relevance
“…One way in which pBS32 might inhibit competence is by the in- hibition of competence gene expression. In laboratory strains, competence genes are expressed in only a subpopulation (16,17,(38)(39)(40). To examine gene expression of a heterogeneous population, the ancestral, laboratory, and cured strains were fluorescently labeled such that the P comK promoter that directs expression of the ComK transcription factor was fused to YFP (lacA::P comK -YFP), while the ComK-dependent P comGA promoter that directs expression of ComGA, an ATPase required for DNA uptake, was fused to mCherry (thrC::P comGA -mCherry) (41).…”
Section: Resultsmentioning
confidence: 99%
“…One way in which pBS32 might inhibit competence is by the in- hibition of competence gene expression. In laboratory strains, competence genes are expressed in only a subpopulation (16,17,(38)(39)(40). To examine gene expression of a heterogeneous population, the ancestral, laboratory, and cured strains were fluorescently labeled such that the P comK promoter that directs expression of the ComK transcription factor was fused to YFP (lacA::P comK -YFP), while the ComK-dependent P comGA promoter that directs expression of ComGA, an ATPase required for DNA uptake, was fused to mCherry (thrC::P comGA -mCherry) (41).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is conceivable that there is a regulatory connection between the hdrM phenotypes associated with growth and natural competence. This result would not be surprising, given that competence escape in Bacillus subtilis is linked to cell growth (Hahn et al, 1995;Haijema et al, 2001). In addition, it has been demonstrated that natural competence in S. mutans is greatly enhanced within the biofilm (Li et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…6A). No septal band of GFP-ComN was found in the competent cells, however, probably because divisome assembly is blocked as a result of competence development (13). Superimposing the ComGA-CFP and GFP- Fluorescence micrographs of membrane-stained wild-type (PY79) and comN mutant (FG1076) bacteria.…”
Section: Resultsmentioning
confidence: 99%